2020
DOI: 10.1186/s13054-020-03255-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of inflammatory parameters and their correlation with disease severity and outcomes in patients with COVID-19 from Wuhan, China

Abstract: Background Coronavirus disease 2019 (COVID-19) is a newly emerging infectious disease and rapidly escalating epidemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pathogenesis of COVID-19 remains to be elucidated. We aimed to clarify correlation of systemic inflammation with disease severity and outcomes in COVID-19 patients. Methods In this retrospective study, baseline characteristics, laboratory findings, and treatments were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 59 publications
14
135
4
5
Order By: Relevance
“…Regarding COVID-19, changes in inflammation stimulation were also revealed to be closely associated with the disease progression and prognosis of COVID-19, which was indicated by hsCRP fluctuations. In previous studies, higher hsCRP fluctuation was related to an increase in the inflammatory response and was associated with disease prognosis in young and middle-aged patients [3] , [9] , [16] , [21] , [26] , indicating a greater inflammatory response in critical patients than severe patients, which supported our finding. Furthermore, worsening of the inflammatory state was not only the main cause of poor COVID-19 prognosis, but this finding could also be extended to other coronaviruses, including severe acute respiratory syndrome (SARS) [27] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding COVID-19, changes in inflammation stimulation were also revealed to be closely associated with the disease progression and prognosis of COVID-19, which was indicated by hsCRP fluctuations. In previous studies, higher hsCRP fluctuation was related to an increase in the inflammatory response and was associated with disease prognosis in young and middle-aged patients [3] , [9] , [16] , [21] , [26] , indicating a greater inflammatory response in critical patients than severe patients, which supported our finding. Furthermore, worsening of the inflammatory state was not only the main cause of poor COVID-19 prognosis, but this finding could also be extended to other coronaviruses, including severe acute respiratory syndrome (SARS) [27] .…”
Section: Discussionsupporting
confidence: 92%
“…Thus this study proposed the association between the worsening of the inflammatory state and ICU admission in young and middle-aged severe patients, which was different from the findings in elderly severe patients. Recently, the preliminary studies reported that hyperactive immune responses mainly manifesting as increased inflammatory markers could be associated with COVID-19 disease severity and outcomes [8] , [9] , [10] . There was a proposed inflammatory model to explain the mechanism by which worsening of the inflammatory state was the main reason for critical COVID-19 in young and middle-aged patients that distinguished COVID-19 development into three stages [11] .…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proinflammatory cytokine and has been proved participate in many inflammatory diseases [ 33 – 35 ]. Many studies showed that inhibition of IL-6 is a promising way to the treatment of inflammatory diseases [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum level of inflammatory marker decrease with the duration of SARS-CoV-2 infection. 13 An anticipated additional decline in level of inflammatory marker by 20% with intervention was used for sample size calculation. Sample size came to be 16 participants in each group with power of 80% (beta error 0.2) and at 95% level of significance (alpha error 0.05).…”
Section: Sample Size Estimationmentioning
confidence: 99%